1150. Cleaning High Touch Surfaces of Patients' Rooms: Make It Easier, and It Simply Gets Cleaner. (26th November 2018) - Martin, Emily T; Dadon, Mor; Lazarovitch, Tsilia; Saadon, Hodaya; Maya, Tal; Jaffe, Katie; Moscovich, Sharon; Zaidenstein, Ronit; Marchaim, Dror
Abstract: Background: The healthcare environment has been established as a reservoir for human pathogens and specifically multidrug-resistant organisms (MDRO). High touch surfaces and fomites in a patient's room mediate transmission between infected and uninfected patients and personnel. Efforts to reduce hospital-associated infections due to MDROs often focus on room cleaning; however, adherence to and thoroughness of cleaning pose significant challenges. Methods: A crossover trial was implemented in January 2016 (for 15 months) at Assaf Harofeh Medical Center (Israel) in four identical medical units. Single-use wipes (Clinell®; universal wipes and sporicidal wipes for rooms of patients with C. difficile ), were compared with common practices which consisted of reusable cloths and bleach (1, 000–5, 000 ppm). Six-month cleaning and intervention periods were used on units in alternating sequences, separated by washout periods. Cleaning was monitored twice a week (bedrail, bedside table, clinical binder, call button, and lamp switch), by a fluorescent marker system (Clinell®). Comparisons used GEE with clustering for room. Staff were surveyed on intervention feasibility, acceptability, and satisfaction. Results: Complete cleaning in all five test locations was found in 23% of 400 total assessments and was more common in the intervention group (34% vs. 12%; OR = 3.7; P < 0.001). Cleaning adherence was highest for the bed rail (71%) and lowest for the call button (38%). The use of wipes had the largest effect on adherence for the light switch (59% vs. 26%; OR = 4.2; P < 0.001). Intervention timing was not associated with overall adherence ( P = 0.10). 94% of staff reported overall satisfaction of "very good" or "excellent, " and 90% of staff reported that use of the wipes shortened the cleaning process. Conclusion: The use of cleaning wipes resulted in greater adherence to room cleaning and the method was reported to be acceptable to staff. Future aims of this large study (over 10, 000 patients were enrolled and data collection not yet completed) are to determine the impact of this intervention on rates of hospital-acquired infections, MDRO acquisitions, and mortality. Disclosures: E. T. Martin, Clinell: Grant Investigator, Research grant. D. Marchaim, Clinell: Grant Investigator, Grant recipient.